Name writing ability not length of name is predictive of future academic attainment. Issue 3 (2nd July 2016) - Copping, Lee T.; Cramman, Helen; Gott, Sarah; Gray, Helen; Tymms, Peter
Abstract: Background: The Performance Indicators in Primary Schools On Entry Baseline assessment for pupils starting school includes an item which aims to assess how well a pupil writes his or her own name. There is some debate regarding the utility of this measure, on the grounds that name length may constitute bias. Purpose, method and design: The predictive validity of this item and its link to name length was investigated with a view to using this item in further assessments. Previous modest scale work from the USA, suggests that name writing ability is a robust indicator which correlates substantively with other known indicators of later reading whilst remaining independent of name length. This paper greatly expanded the sample size and geographical coverage and, rather than concurrent measures, the predictive validity of the item is assessed. The sample includes children from England, Scotland and Australia ( N  = 14932), assessed between 2011 and 2013. Potential confounding factors that are analysed include age, geographical region and ethnicity. Findings and conclusions: The evidence suggests that the name writing item is a robust measure, with good predictive validity to future academic outcomes in early reading, phonological awareness and mathematics. The length was not related to the ability to write one's own name nor was it predictive of future outcomes.